2011
DOI: 10.1089/dna.2010.1139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Profile of Periodontal Ligament Cells Subjected to Cyclic Compressive Force

Abstract: Cyclic compressive force is an important mechanical stimulus on periodontal ligament (PDL). The differential expression of genes in PDL cells is thought to be involved in the remodeling of periodontal tissues subjected to mechanical stress. However, little is known about differentially expressed genes in PDL cells under cyclic compressive force. In our study, human PDL cells were subjected to 4000 μ strain compressive stress loading at 0.5 Hz for 2 h. The effect of mechanical stress on PDL cells proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Although several studies investigated mRNA profiles, the comparison of gene expression in hPDLs subjected to different force types is lacking 10,38,39 . Uniaxial cyclic strain application induced genes related to cell cycle, apoptosis, and proliferation in hPDLs 40 . In contrast, static compressive force regulated genes related to the ECM, inflammatory cytokines, and cell growth 10 .…”
Section: Discussionmentioning
confidence: 95%
“…Although several studies investigated mRNA profiles, the comparison of gene expression in hPDLs subjected to different force types is lacking 10,38,39 . Uniaxial cyclic strain application induced genes related to cell cycle, apoptosis, and proliferation in hPDLs 40 . In contrast, static compressive force regulated genes related to the ECM, inflammatory cytokines, and cell growth 10 .…”
Section: Discussionmentioning
confidence: 95%
“…DLC1 is vital for normal development because null mutations in the gene result in embryonic lethality in mice and flies. It is also involved in insulin signaling and the pathogenesis of coronary spastic angina and is among four genes that negatively regulate periodontal ligament cell proliferation (5659). …”
Section: Dlc1 a Potent Tumor Suppressor Gene In Hepatocellular Carcinomamentioning
confidence: 99%
“…8 In the PDLCs, however, mechanical stimuli promote cell proliferation by influencing the duration of the S phase and mitotic activity. 25 Moreover, previous studies have shown that the osteoblastic marker expression increases in PDLCs under pressure, 26,27 while in the current study, these markers were reduced in cementoblast cells. The different characterization of these two cells may result in their different responses to compressive force.…”
Section: Discussionmentioning
confidence: 40%